Parents' Parenting Pattern of Study Discipline for Accounting Major Students at SMKN 1 Makassar - Chadijah Jul Pancawati Maulana; Sahade Sahade; Muhammad Azis (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of parenting style on the learning discipline of students in the accounting expertise program at SMKN 1 Makassar. The sampling technique uses the Proportionate Stratified Random Sampling technique. Data collection techniques used are questionnaires and documentation. Data analysis was carried out by using descriptive analysis of percentages, instrument testing, and hypothesis testing. Based on the results of data analysis, it was obtained that the simple linear regression equation model Y = 20.856 + 0.368X, which means that for each addition of 1 value of parenting, the value of learning discipline increases by 0.368. The coefficient of determination (r2) is 40.7% which means parenting style has an influence on learning discipline of 40.7% and the remaining 59.3% is influenced by other factors. The Pearson Product Moment correlation coefficient is 0.638 which is in the strong category, which means that there is a strong relationship between parenting styles and student learning discipline. While the results of the t-test analysis obtained a significant value of 0.000 <0.05, which means parenting style has a significant effect on learning discipline, thus the hypothesis is accepted.